Investigating errors made by English as a foreign language students during online collaborative writing - Moonma , Jitlada (Asian Journal of Education and Training, 2024)
This study focused on investigating common writing errors made by a group of Thai students who participated in online collaborative writing using Google Docs, and understanding their satisfaction and attitudes on this writing approach. The participants consisted 32 Thai first-year English major students who were purposively selected from their Writing I course. The researcher collected and analyzed eight argumentative pieces of writing, identifying a total of 484 errors. The most frequently occurring error areas were incomplete sentences (15.75%), spelling mistakes (13.50%), and word choice issues (12.25%), with grammatical errors being the most prevalent (72%). Following grammatical errors were lexical (12%) and mechanical errors (4%). To gauge students' satisfactions and attitudes, a questionnaire and semi-structured interviews were employed. The findings revealed that the students were highly satisfied with online collaborative writing with an average satisfaction score of 3.50. Overall, the students exhibited a positive attitude towards online collaborative writing, finding it useful due to its flexibility in terms of allowing them to work from anywhere at any time and for its ability to boost their motivation. The study's findings provide valuable insights for English teaching professionals in Thailand to consider when instructing students in writing.